Comparability of Single Measurements of Serum Testosterone to the 24‐Hour Cavg in Patients Using Testosterone 2% Solution. (1st November 2014) - Muram, David; Baygani, Simin
Abstract: Introduction: Efficacy of testosterone replacement therapy is determined by the proportion of men with 24‐hour average serum testosterone concentration (Cavg ) in the normal range. In clinical practice, monitoring and dose adjustments are based on single testosterone measurements; however, how single measurements reflect Cavg is unclear. Aim: This post‐hoc analysis evaluated whether single serum testosterone measurements and Cavg from the same day are both in the normal range in men receiving testosterone replacement therapy. Methods: In an open‐label, multicenter, titration trial, androgen‐deficient men (N = 155) were started on 60‐mg daily morning dose of testosterone 2% solution (Axiron®, Eli Lilly and Company, Indianapolis, Indiana, USA) applied to axillae (30 mg/axilla). Serum testosterone Cavg was determined on Days 15, 60, and 120. If necessary, dose was adjusted to maintain Cavg in the normal range (300–1, 050 ng/dL). This analysis included subjects (n = 105) whose Cavg was within the normal range on Days 15, 60, and 120. Main Outcome Measures: Proportion of men with normal serum testosterone levels at 2, 4, or 8 hours post‐dose on Days 15, 60, and 120. Results: Greater than 93% of subjects had testosterone serum levels within the normal range 2, 4, or 8 hours post‐dose on at least 1 day. In subjects with blood samples available from Days 15 and 60 or Days 15 and 120, 71.1% to 79.8% had normal levels at 2, 4, or 8 hours post‐dose on both days, and in subjects with blood samples available from Days 15, 60, and 120, 63.9% to 68.8% had normal levels at 2, 4, or 8 hours post‐application on all 3 days. Conclusion: Less than 70% of single testosterone measurements made on 3 separate days were concordant with same‐day Cavg for all 3 days. These findings, which are specific for testosterone 2% solution, indicate that single measurements do not always reflect the 24‐hour Cavg, and may possibly lead to inappropriate dose adjustments.